Co-occurrence of Frailty, Possible Sarcopenia, and Malnutrition in Community-Dwelling Older Outpatients: A Multicentre Observational Study - Siti Setiati; Kuntjoro Harimurti; Ika Fitriana; Noto Dwimartutie; Rahmi Istanti; Muhammad Khifzhon Azwar; I Gusti Putu Suka Aryana; Sri Sunarti; Agus Sudarso; Dina Aprillia Ariestine; Lazuardhi Dwipa; Novira Widajanti; et al. (Annals of Geriatric Medicine and Research)
Background The co-occurrence of frailty, sarcopenia, and malnutrition was well studied in inpatient and nursing home settings, which was associated with higher risk of all-cause mortality. Multicentre data in community-dwelling outpatient setting were lacking. We aimed to find the prevalence of frailty, possible sarcopenia and malnutrition, their overlap and the associated factors in community-dwelling older outpatients. Methods We collected data from community-dwelling outpatients aged ≥60 years in Indonesian geriatric care centres to conduct this cross-sectional study with bivariate and multivariable analyses. Frailty, possible sarcopenia, and malnutrition diagnoses were based on FRAIL scale, Asian Working Group for Sarcopenia 2019 consensus, and Mini Nutritional Assessment Short Form, respectively. Results The prevalence of frailty, possible sarcopenia, and malnutrition in community-dwelling older outpatients were 13.6%, 45.5%, and 5.3%, respectively. The prevalence of co-occurrence of frailty, possible sarcopenia and malnutrition was 3.3%. It was associated with transient ischemic attack (TIA) and cerebrovascular accident (odds ratio [OR]=5.53, 95% confidence interval [CI] 1.48–20.61), cognitive impairment (OR=3.70, 95% CI 1.21–11.31), and dependent functional capacity (OR=11.62, 95% CI 3.38–39.99). Overlap of three evaluated syndromes was found in 24.1%, 7.2%, and 61.3% of subjects with frailty, possible sarcopenia, and malnutrition, respectively. It was characterized by a substantial proportion of female sex, older adults with low educational attainment, diabetes mellitus, hypertension, cognitive impairment, multimorbidity, and dependent functional status. Conclusion Approximately 1 in 30 community-dwelling older outpatients had overlapping frailty, possible sarcopenia, and malnutrition. The condition is associated with TIA and cerebrovascular accident, cognitive impairment, and dependent functional capacity. Standardized screening in community-dwelling older population is necessary.